Identification of Key microRNAs and Genes in Infantile Hemangiomas - Fu, Cong; Yang, Kun; Zou, Yuqing; Huo, Ran (Frontiers in Genetics, 2022)
Infantile hemangiomas (IHs) are the most frequent vascular tumors that occur during infancy. Microribonucleic acids (miRNAs) have been demonstrated as critical regulators of gene expression in various diseases. However, the function of miRNAs in IH still remains largely unknown. In the present study, we performed a miRNA microarray analysis of IH and identified 68 differentially expressed miRNAs (DEMs) . In addition, miRNA-gene networks and protein-protein interactions were constructed, and the hub miRNAs and genes of IH were screened out. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis were used for biological analysis of DEMs and differentially expressed genes(DEGs). The pathway enrichment analysis of DEMs revealed several tumor-related pathways, including proteoglycans in cancer, signaling pathway regulating pluripotency of stem cells and TGF-beta signaling pathway. DEGs were mainly enriched in biological processes, including intracellular signal transduction, cell adhesion, and cell death. KEGG pathway analysis indicated that DEGs were enriched in tumorigenesis- and angiogenesis-related pathways such as proteoglycans in cancer, MAPK signaling pathway and Rap1 signaling pathway. Collectively, this study first established a comprehensive miRNA-gene network in IH, which should provide novel insights into IH pathogenesis and be beneficial to the understanding of neovascularization-related disorders.